Perceptions and understandings of mental health from three Sudanese communities in Canada. Issue 3 (3rd July 2017) - Este, David; Simich, Laura; Hamilton, Hayley; Sato, Christa
ABSTRACT: As Canada becomes increasingly ethno-culturally diverse, health and human services professionals are challenged to provide mental health services that effectively meet the needs of newcomer populations. Currently, there is a dearth of literature focused on the ways in which members of Sudanese communities in Canada understand or make meaning of the constructs of mental health and illness. The purpose of this article is to explore the perceptions and understandings of mental health and illness through the lens of Southern Sudanese community members in Toronto, Ontario, and Calgary and Brooks, Alberta . Thirty-two in-depth interviews across the three sites were completed using a semi-structured interview guide. Multi-lingual Sudanese research assistants conducted the interviews. Using an inductive data analysis approach, seven major themes emerged related to the focus of the study: Sudanese perceptions and understandings of mental health; social isolation; neglect of personal hygiene; stigma; mental health as multi-dimensional; stress as a cause; and positive mental health. The paper concludes with implications for mental health practitioners.